Preface - Itao Tao; Perskaya Victoria; Morkovkin Dmitry; Suyunov Abdusali (E3S Web of Conferences)
As part of this information, the results of the IV International Conference on Ensuring Sustainable Development: Ecology, Earth Science, Energy and Agriculture (AEES2024) are presented.